Thermal analysis of friction stir welding with a complex curved welding seam - Meyghani, B. (Materials and Energy Research Center, 2019)
Friction stir welding (FSW) can be defined as a green technology, because the consumption of energy during this process is less than other welding methods. In addition, during the process there is no gas, filler material or other consumables. It should be noted that, complex curved shapes are now commonly used in different industries in a bid to have lightweight structures. According to the above-mentioned descriptions, several investigations into the potential benefits of adopting Friction Stir Welding (FSW) in the production and joining different materials are being undertaken. The work presented in this paper is focused on thermal behavior of the curved FSW and its benefits for the green technology. Due to the robust nature of FSW process aluminum 6061-T6 alloy has been selected as the welding material. The results of the study showed that, the total peak temperature value of 300°C happened at time, t = 3 s at the plunge stage (outside of the welding seam). Meanwhile, at the dwell stage (between t = 3 s to t = 5 s), there is a stable situation in the amount of the generated heat from the plastic deformation as well as the contact shear stress at the tool-workpiece contact interfaces, thus the interfacial temperature is found to be stable. By the end of the dwelling step, the total generated heat is stable to the maximum value of 300°C. At the step time of t = 12.8 s, the temperature is distributed asymmetrically across the workpiece until the time step of 19.6 s which at this point the asymmetric contour expanded in the stir zone. © 2019 Materials and Energy Research Center. All rights reserved.